The Role of Anti-dengue Virus NS-1 and Anti-protein Disulfide Isomerase Antibodies on Platelet Aggregation in Secondary Dengue Infection - Andhika Rachman; A.R. Harahap; R.M. Widhyasih (Acta Medica Indonesiana)
Aim: to observe the correlation between anti-NS-1 and anti PDI antibodies against platelets function disorder on secondary dengue infection. Methods: 50 patients with secondary DV infection according to WHO criteria were observed by a cross sectional study. Patient’s blood was collected on day 3, 5 and 7 after fever onset. Platelets aggregation test was done to prove the possibility of platelets dysfunction. Anti-NS-1 and anti- PDI antibodies were determined by solid phase ELISA. Results: the inhibition of platelets aggregation was increased among day of observation. Means value of inhibition on day 3 is 46.6%, day 5 is 52.5% and day 7 is 56%. There is a significant difference (p<0.05) of inhibition of platelet aggregation value between days of observation. The antibodies against NS-1 DV and PDI were detected in all 50 sera with the positive rate of 90% develop NS-1 antibodies and 72% of PDI antibodies, on day 3 of symptoms. The highest OD of NS-1 antibodies is detected on the day 3 and decreased on day 7. The OD of PDI antibodies was increased on day 3 and still increasing on day 7. There is a significant correlation between anti NS-1 and PDI antibodies (r=0.386-0.490), while the differences of OD between observation days are not significant (p>0.05). Conclusion: the kinetics profile of NS1 and PDI antibodies responses, which were detected by the third day of symptoms. Dengue patients’ sera inhibited platelets aggregation. NS-1 antibodies and PDI antibodies might have a role on the platelets aggregation dysfunction; however, there is no correlation between them. It is possible that other mechanism involve in the inhibition of platelets aggregation.